A new online testing technique for reversible circuits. Issue 1 (4th March 2022) - Mondal, Joyati; Das, Debesh Kumar
Abstract: Any technology offering zero power dissipation must be reversible. A reversible circuit can be envisaged as a cascade of reversible gates only, such as Toffoli gate, which has two components: k control bits and a target bit ( k ‐CNOT), k  ≥ 1. Analysing testability issues in a reversible circuit is an important phenomenon. A new online design‐for‐testability (DFT) technique for reversible circuits is proposed. The authors' method yields less overhead in terms of quantum cost as compared to the previous online approaches.